Foreign body aspiration masquerading respiratory tract infection - Ashraf, Mohd; Bhat, Sayar Ahmed; Ahmed, Parvez; Riyaz, Anisa; Shafi, Mohd (Indian Journal of Case Reports, 2019)
Foreign body (FB) aspiration is a potentially life threatening event where prompt and precise action can turn tears into smiles. We report a case of an eight-year school going boy, with one-month old history of foreign body aspiration. The boy was treated as a case of respiratory tract infection. It was due to reappearance of symptoms and signs of chest infection supported by chest radiography that prompted for the CT-chest. It was followed by rigid bronchoscopy to confirm the therapeutic diagnosis of FB aspiration. This case report highlights the importance of detailed thoughtful history in pediatrics particularly to FB aspiration.